ANALISIS TEKNO EKONOMI PEMANFAATAN LIMBAH BUAH-BUAHAN SEBAGAI MIKRO ORGANISME LOKAL (MOL) - Muhammad Nur; Alfinur Khairi (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
The high volume of garbage in the city of Pekanbaru, especially organic garbage, has led to the idea of utilizing the garbage to become a more useful thing, where it can be used as material in making MOL (local organism). TheÂ  utilization of MOL (local organism) it self is very beneficial for farmers because the ingredients that used come from the organic materials, and the costs that we used are less than buying commercial fertilizers.The purpose of this study is to find outÂ  the process of making MOL, to know the nutrient test values in MOL from the waste of fruits, to know the techno-economics of making MOL from the waste of fruits. The method that used is Variable Costing to calculate The Cost of Production and the Random Duplicate Design method to determine the treatment of MOL. The results of the laboratory test showed that Treatment A on the 3rd repetition with a level of 100 ml EM-4 had the best results with a value of Nitrogen 0.0010%, Fospor 0.000014%, and Potassium 0.000022%. The cost of production is Rp 21,000 / Liter and Break Even Point is 4 Liter that relased in Rp 69,686.49